Bir Ekorekreasyon Faaliyeti Olarak Yoga Turizmi Üzerine Bir İnceleme - SARI, Yaşar; ŞENEL, Elif (Uluslararası Kırsal Turizm ve Kalkınma Dergisi (IRTAD) E-ISSN: 2602-4462, 2019)
The human being, which is part of social life, is divided into working time and non-working time (leisure time).Although there are separate time periods on a time basis, run time and leisure time are influencing each other. With the increasingly short working hours, the advance of technology and the expansion of mass communication network, the working time in human life has begun to decrease and thus the increase in leisure time has become a factor. This increase in leisure time reveals the concepts of time-honoured and effective use. In active time use; recreational activities that entertain, rest and satisfy the individual from all sides come to the forefront in addition to efficient and active use of time. Recreational activities include pleasure, entertainment, skill development and socialization, as well as individual abstinence and relaxation. Because of these features, recreational activities are an indispensable point of human life and the demand for these activities is increasing day by day. In today’s conditions, individuals prefer recreation areas where they can enjoy and listen, as well as areas where environmentally high spiritual, physical, and physical calmness can be reached and relaxed. Because they are subjected to recreational activities in which they can listen to the souls of the individual tired from the tiredness, the sadness and the stress of life and stay with them. It has emerged as a trendy recreational activity, and today yoga is becoming popular both as a widespread activity and as an alternative tourism. Many people in our country are traveling to the yoga centres that have been rapidly increasing in number in recent years in order to be able to yoga and meditate in order to purify both body and mind from the noises, pollution and rush of urban life. From this point yoga tourism as a ecorecreation’s activities in this study, characteristics, camps, concepts such as yoga tourists and yoga practices by examining the literature, the location of yoga tourism in Turkey and the importance of going to be analysed.